Power training build your most powerful body ever with Australis's Body Coach - Collins, Paul (The body coach series, 2008)
Offers an easy-to-follow, illustrated guide to drills, test, and training routines - used by Olympic and other world-class athletes - that helps improve power and performance. This book contains more than 80 exercises to develop training programmes that helps keep the readers fit and strong